The cervantes lava flow geomorfology, irazú volcano (costa rica): description of the central america`s greater lava flow field - Alvarado, Guillermo E. (2011)
The Cervantes lava flow field, on the southeastern flank of Irazú volcano, is the most recent and large effusive event dated at this volcano. The Cervantes lava flow actually consists of two different bi-modal lava flow fields. The Western composite lava field (10.85 km2, 0.18 ± 0.1 km3) has a basaltic (SiO2: 50.71-52.06%; MgO: 8.13- 9.50%) and basaltic andesite composition due to magma mixing (SiO2: 52.90-53.42%; MgO: 6.71-7.12%) and is older in age (57 ka ± 13 ka years B.P.). The Eastern composite lava field (28.14 km2, 1.14 ± 0.25 km3) has a basaltic andesite composition (SiO2: 55.54-56.58%; MgO: 4.4-5.26%) and is younger (~16 840 years B.P.). The Cervantes flows present a distinctive morphology of channels and levées, and hummocks hills. Their internal structure is composed of several massive lava units inter-layered by auto-breccias (including rare lava balls). The Western composite rubbly lava flow is thinner (< 20 m thick) and presents a clinker surface of overlapping flows. On the other hand, the Eastern is a composite (several flow units) rubbly and blocky lava flow, and it is thicker (> 20 m), particularly when the lava became confined, achieving a thickness of 150 m, and resulting into a complex joint prismatic structure that gave rise to the Cachí paleo- lake. Although the Western lava flow-field is more basic en composition (possibly more fluid), its smaller dimensions could be the result of a lower lava effusion rate, a higher cooling rate, and/or that the lava supply ceased. Instead, the Eastern basaltic andesite lava flow-field, originated from vents at lower altitudes, is thicker, longer and widespread lava field, with the larger sizes of levees, are presumable related to long-term effusion and/or higher average flow rate. The Eastern lava field presents areas without lava deposition (kipukas) and several depressions of different forms, which appear to be related to a crude snake pattern, and therefore could be the result of the lava flow filling fluvial valleys. The south flank of Irazú has a conjugated (N34oE and N26oW, σ1 being oriented N04°E) 2 km-long fissure system of craters and cinder cones, which was the source of the Cervantes lava fields. These volcanic trends are potential future sites for vertical feeder dikes and new effusive events.